Las TICs en el Perú desde el desarrollo sostenible: una propuesta para las zonas rurales - Guerrero Chanduví, Dante A. (2011)
At the World Summit on the Information Society (2003 and 2005) defines ICT as the main tools to generate the necessary knowledge to achieve the development of a country. It makes increase the economic and political efforts to spread the ICT. In Peru is a digital divide between rural and urban areas, which becomes the main obstacle to turn the country into an Information Society that carries its own development. There is a need for efficient ways to carry out the projects to disseminate the infrastructure, the usage and the skills related to ICT in rural areas of the country in order to reduce the digital divide. The implementation of the LEADER approach, as the most appropriate for this type of projects, will be analyzed in a Peruvian rural area.